2023
DOI: 10.1021/acsomega.3c03157
|View full text |Cite
|
Sign up to set email alerts
|

Combined First-Principles and Experimental Study on the Microstructure and Mechanical Characteristics of the Multicomponent Additive-Manufactured Ti–35Nb–7Zr–5Ta Alloy

Abstract: New β-stabilized Ti-based alloys are highly promising for bone implants, thanks in part to their low elasticity. The nature of this elasticity, however, is as yet unknown. We here present combined first-principles DFT calculations and experiments on the microstructure, structural stability, mechanical characteristics, and electronic structure to elucidate this origin. Our results suggest that the studied β Ti−35Nb−7Zr−5Ta wt % (TNZT) alloy manufactured by the electron-beam powder bed fusion (E-PBF) method has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Ab-initio calculations by Grubova et al provide comprehensive insights into optimizing dopant elements in titanium alloys for biomedical applications. Focusing on the Ti–35Nb–7Zr–5Ta (TNZT) alloy produced via electron-beam powder bed fusion (E-PBF), the study explains the low elasticity observed in β-stabilized Ti-based alloys.…”
Section: Alloy Design Conceptsmentioning
confidence: 99%
“…Ab-initio calculations by Grubova et al provide comprehensive insights into optimizing dopant elements in titanium alloys for biomedical applications. Focusing on the Ti–35Nb–7Zr–5Ta (TNZT) alloy produced via electron-beam powder bed fusion (E-PBF), the study explains the low elasticity observed in β-stabilized Ti-based alloys.…”
Section: Alloy Design Conceptsmentioning
confidence: 99%